INVESTIGATION OF GMAW BY SIMULATION MODELLING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The thermal and deformation cycle during welding is directly reflected on the formation of the welded joint and the imperfections that can occur in any specific case. The simulation modelling of the heating and cooling processes makes it possible to determine the temporary and residual stresses in the welded joint. When solving the thermal and deformation tasks, it is essential to use data on the characteristics of the material in the entire temperature range in which the studied processes take place. At the same time, these data are often not available. In order to be able to use simulation solutions in practice, the standard EN ISO 18166 provides for calibration of thermal and deformation models before they are applied to the welded structure. In this study, the calibration of a thermal model applicable to MIG / MAG welding is considered. The heat source is superficial and axisymmetric. The calibration parameters are efficiency, effective radius of the heat source and coefficient determining the deviation from the normal central Gaussian distribution. Experimental data on the bead shape were used for the calibration process. The obtained simulation results for the temperature field are compared with the experimental ones. Sensitivity analysis of the solution with respect to the material characteristics was performed.